Hukum Pidana Dalam Menanggulangi Tindak Pidana Internet Gambling Di Indonesia - Khoilul Ahmad Jidan; Riska Andi Fitriono (Lembaga Pengembangan Kinerja Dosen, 2024)
Internet gambling crimes in Indonesia are increasing from year to year. This phenomenon is a bad thing for the Indonesian people. Therefore, the author conducted research which aims to find out how criminal law tackles internet gambling in Indonesia. By using normative research methods. In this legal research, the author uses primary legal materials and secondary legal materials obtained through literature studies that are appropriate to the topic of discussion that the author has taken. Based on the research results, it can be concluded that internet gambling regulations in Indonesia are regulated in Article 27 Paragraph (2) and the threats are regulated in Article 45 Paragraph (3) of the ITE Law. However, the regulations in this article do not clearly regulate witnesses for internet gaming players. This law only contains services used to carry out internet gambling. Law No. 1 of 2023 concerning the Criminal Code can be a solution to overcome the weak response to internet gambling crimes in Indonesia because acts committed digitally have been accommodated in this law.